2023
DOI: 10.1007/s11914-023-00815-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Peripheral Nervous System in Skeletal Development and Regeneration: Controversies and Clinical Implications

Abstract: Purpose of Review This review examines the diverse functional relationships that exist between the peripheral nervous system (PNS) and bone, including key advances over the past century that inform our efforts to translate these discoveries for skeletal repair. Recent Findings The innervation of the bone during development, homeostasis, and regeneration is highly patterned. Consistent with this, there have been nearly 100 studies over the past century that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 133 publications
0
0
0
Order By: Relevance
“…Though our data and others show that local nerves are not necessary for this response, it remains possible that changes in nerve function are sufficient to modulate the amount of bone formed. This could be through the hypersecretion of local neurotransmitters or through secondary changes in nervous system function throughout the body (7) . Nerve growth factor (NGF) is one of the most highly and consistently upregulated genes in bone after compressive loading of the limbs (16,37,38) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Though our data and others show that local nerves are not necessary for this response, it remains possible that changes in nerve function are sufficient to modulate the amount of bone formed. This could be through the hypersecretion of local neurotransmitters or through secondary changes in nervous system function throughout the body (7) . Nerve growth factor (NGF) is one of the most highly and consistently upregulated genes in bone after compressive loading of the limbs (16,37,38) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RadialQuant of periosteal axon density showed a trending interaction effect of load and radial bin (2-way ANOVA, p=0.087), indicating possible spatial redistribution or mild sprouting of axons following mechanical loading. In addition to effects on nerves, NGF can activate TrkA receptors on endothelial cells and potentially also osteolineage cells to regulate do novo vasculogenesis and bone formation directly (7,39) . Consistent with this, recent work found that when the high-affinity NGF receptor TrkA was blocked globally throughout the body, this prevented 41% of the load-induced increase in BFR, 16% of the load-induced increase in mineralizing osteoblasts, and 31% of load-induced increase in osteoblast activity (16) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in line with recent studies that have highlighted the potential relevance of neuroskeletal function to bone health in settings of development, homeostasis, and regeneration (reviewed in refs. 14,15). Together, this has prompted the hypothesis that neural dysfunction, through the onset of DPN, may be responsible for the onset and progression of diabetic skeletal disease -representing a possible unified target point for treatment of both disorders.…”
Section: Introductionmentioning
confidence: 99%